Lymphangioleiomyomatosis: New Concepts in Pathogenesis, Diagnosis, and Treatment - Meraj, Riffat; Wikenheiser-Brokamp, Kathryn A.; Young, Lisa R.; McCormack, Francis X. (Seminars in Respiratory and Critical Care Medicine, 2012)
Lymphangioleiomyomatosis (LAM) is a slowly progressive lung disease that is associated with mutations in tuberous sclerosis complex genes, infiltration of the pulmonary parenchyma and lymphatics with neoplastic smooth muscle cells, extensive tissue remodeling and architectural distortion of the lung, and tumors of the chest and abdomen, including lymphangiomyomas and angiomyolipomas. LAM occurs in women in the general population and in patients of both genders with tuberous sclerosis. Overt clinical manifestations of LAM occur almost exclusively in females, however, and include progressive dyspnea on exertion, recurrent pneumothorax, and chylous effusions. The molecular basis of LAM has been extensively characterized over the past decade, resulting in the development of a targeted therapy. This article reviews emerging approaches to the diagnosis and treatment of LAM.
Keywords: lymphangioleiomyomatosis; lymphangiomyomas; angiomyolipomas; tuberous sclerosis